2017
DOI: 10.21621/sajms.2017111.01
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Project Teamwork on Project Success in Pakistan

Abstract: The contribution of project teamwork is based on project members toward project success has remained unattended in prior literature. This paper highlights the importance of project teamwork for the project success and argues that leader alone cannot successfully complete a project. This study is based upon Higher Education Commission (HEC)'s projects in Pakistan and data has been collected from project leaders regarding performance and contribution of project teamwork toward project success. The study hypothes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Through teamwork, projects achieve better project value due to synergistic efforts of the team. The result is similar to the study of Iqbal et al (2017).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Through teamwork, projects achieve better project value due to synergistic efforts of the team. The result is similar to the study of Iqbal et al (2017).…”
Section: Discussionsupporting
confidence: 90%
“…Teamwork: A team can be a group of persons with varying knowledge, expertise, and abilities to accomplish tasks to achieve a common goal (Ji and Yan, 2020). Teamwork represents the capability of a team to work unitedly in a cooperative setting to achieve synergistic results (Iqbal et al, 2017). Project teamwork has been recognized as an essential factor in improving project success (Yang et al, 2013).…”
Section: Literature Review and Theoretical Backgroundmentioning
confidence: 99%
“…From the responses to the questionnaire, it is possible that this team had minimum requirements for success, such as interdisciplinary technical skills and other critical personal skills, such as creativity and knowledge (Iqbal et al, 2017). According to our analysis, this team obtained a degree of maturity similar to the others, including the winner team.…”
Section: Discussionmentioning
confidence: 86%
“…Our results are in accordance with literature, which validates the substantial influence of team performance. Iqbal et al (2017) argued that project teamwork is considered a critical factor for project acceptance and success. The findings reflected that the performance of the project team has a significant impact on project success.…”
Section: Discussionmentioning
confidence: 99%
“…The existing literature highlighted the significant role of team performance on project success. Iqbal et al (2017) questioned whether team performance affects project success. They found that teamwork has become a key element and significantly augments greater project success.…”
Section: Team Performance and Project Successmentioning
confidence: 99%